2013
DOI: 10.1080/09649069.2013.774764
|View full text |Cite
|
Sign up to set email alerts
|

When legal rights are not a reality: do individuals know their rights and how can we tell?

Abstract: Public knowledge of rights has been the subject of a number of empirical enquiries over the last decade. In England and Wales, knowledge of rights and its relationship with an individual's capacity to ‘self-help’ and ‘self-represent’ when faced with a civil justice problem has become the subject of renewed attention following changes to legal aid which, from March 2013, will see the availability of legal advice and representation dramatically reduced. Previous studies focusing on public knowledge of rights in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 30 publications
0
13
0
1
Order By: Relevance
“…The perception of mothers together with their children as subjects who hold rights can help them to develop their potential and role, as well as in the construction of citizenship, helping reduce the distance between those exposed by laws and the concrete reality of life (7,12) .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The perception of mothers together with their children as subjects who hold rights can help them to develop their potential and role, as well as in the construction of citizenship, helping reduce the distance between those exposed by laws and the concrete reality of life (7,12) .…”
Section: Discussionmentioning
confidence: 99%
“…Studies have also emphasized the importance of knowledge of rights by persons related to the capacity of care and self-care (12) , understanding the child as being entitled to rights (6) , to the way rights are recognized by the families (13) and its benefits for clinical practice (4) .…”
Section: Introductionmentioning
confidence: 99%
“…In this type of case, the legal clinic can inform people about their rights and what they can expect from, for example, the authorities. The classic Norwegian legal aid study (Eskeland and Finne 1973) and more recent international studies (Curran and Noone 2008;Denvir et al 2013) indicate that people rarely know their rights or what they are entitled to. Furthermore, research has shown that people often do not see their problems as legal ones (Sandefur 2009).…”
Section: Voluntary Student Legal Clinicsmentioning
confidence: 99%
“…Gathering information on the general population is necessary. However, general population surveys are expensive, and time consuming to conduct, and most individuals do not have an in-depth knowledge of legal processes and procedures (Balmer et al 2010;Denvir et al 2013). Thus, traditional examinations of knowledge or legal experience are not applicable.…”
Section: Challenges To Measurement Of Legal Empowermentmentioning
confidence: 99%